COMPARATIVE ASSESSMENT OF SERUM ALANINE AMINOTRANSFERASE (ALT) AND ASPARTATE AMINOTRANSFERASE (AST) LEVELS IN HEPATITIS B AND HEPATITIS C PATIENTS (Frontier in Medical and Health Research, 2026)
Background and Objectives: Major viral illnesses that impact the liver include hepatitis B and hepatitis C, both of which are significant contributors to chronic liver illness globally. Both infections cause hepatocellular damage, which results in increased serum levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT). These liver enzymes are crucial biochemical indicators that are used to gauge the degree of liver inflammation and the course of the illness. The purpose of the current research was to compare serum ALT and AST levels in patients with Hepatitis B and Hepatitis C.Methodology: Khan Laboratory in Sargodha, Pakistan, conducted a cross-sectional analytical investigation. The study included a total of 60 patients who had received a diagnosis of either hepatitis B or hepatitis C. Using the Biolis 24i fully automated chemistry analyzer, serum ALT and AST levels were measured in blood samples obtained in an aseptic environment. SPSS version 26. 0 was used for data analysis. We did a paired t-test and correlation analysis after computing the Mean ± SD. A p-value of less than 0. 05 was deemed statistically significant.Results: The average serum ALT concentration was 941. 23 320. 57 U/L, while the average AST level was 819. 67 320. 53 U/L. With a mean difference of 121. 57 U/L (p < 0. 001), statistical analysis revealed a significant difference between ALT and AST levels. Between ALT and AST values, there was a really high positive correlation (r = 0. 992, p < 0. 001). The results showed that hepatitis patients have considerable liver inflammation and hepatocellular damage.Conclusion: According to the study's findings, ALT and AST are both significant biochemical indicators for determining liver damage in individuals with hepatitis B and hepatitis C. ALT demonstrated significantly greater elevation than AST, which is indicative of higher liver specificity. In viral hepatitis patients, a combination of ALT and AST assessment offers helpful clinical information for illness monitoring and treatment.